2020
DOI: 10.2478/ceer-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Reliability-Based Safety Evaluation of the BISTOON Historic Masonry Arch Bridge

Abstract: This research examines the probabilistic safety assessment of the historic BISTOON arch bridge. Probabilistic analysis based on the Load-Resistance model was performed. The evaluation of implicit functions of load and resistance was performed by the finite element method, and the Monte-Carlo approach was used for experiment simulation. The sampling method used was Latin Hypercube. Four random variables were considered including modulus of elasticity of brick and infilled materials and the specific mass of bric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…FE analysis of historical structures using micro-model and macro-model methods leads to accurate results [6]. Many studies have used the macro-model method as constitutive law of masonry materials and evaluate their structural behavior [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][18][19][20][21][22][23][24][25]. In this method, the components of 4 Outline procedure for reliability assessment under wind and earthquake hazards masonry materials (unit and mortar) and joints surfaces are not modeled separately still modeled as a homogeneous and continuous material with the same mechanical characteristics.…”
Section: Fe Discretization Of Gaskar Minaretmentioning
confidence: 99%
See 1 more Smart Citation
“…FE analysis of historical structures using micro-model and macro-model methods leads to accurate results [6]. Many studies have used the macro-model method as constitutive law of masonry materials and evaluate their structural behavior [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][18][19][20][21][22][23][24][25]. In this method, the components of 4 Outline procedure for reliability assessment under wind and earthquake hazards masonry materials (unit and mortar) and joints surfaces are not modeled separately still modeled as a homogeneous and continuous material with the same mechanical characteristics.…”
Section: Fe Discretization Of Gaskar Minaretmentioning
confidence: 99%
“…In this section, the procedure established in this paper is to examine the probability failure and its corresponding RI ( ) of the minaret under earthquake action presented. The load-resistance (L-R) method utilized in structural reliability assessment in many researches [21,22,[28][29][30][31][32][33][34], also used in the present study. A normal distribution function N(µ, σ) is chosen to define the statistical properties of random variables (RVs).…”
Section: Reliability Analysismentioning
confidence: 99%
“…Thus, over the past few decades, studies focused on multi-hazard vulnerability analyses have gained momentum [8]. Accordingly, multi-hazard fragility analysis is widely reported in existing literature considering earthquake, tsunami, flood, scour, and other forces [9][10][11][12][13][14][15]. Mosleh et al [16] performed seismic vulnerability of pre-1990 concrete bridge and developed analytical fragility functions.…”
Section: Introductionmentioning
confidence: 99%
“…Although an extensive review of the state of the art on the subject is not the aim of this paper, several investigations and studies can be found in the technical literature; in most cases these studies are aimed at monitoring the state of the infrastructures in order to assess their safety. The classical studies in the structural field aimed at evaluating the mechanical behavior of the artifacts, the characterization and state of conservation of the component materials, their seismic vulnerability and structural modeling for the safety of road and railway bridges [9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%